Is Two Better than One? Limb Activation Treatment Combined with Contralesional Arm Vibration to Ameliorate Signs of Left Neglect - Pitteri, Marco; Arcara, Giorgio; Passarini, Laura; Meneghello, Francesca; Priftis, Konstantinos (Frontiers in Human Neuroscience, 2013)
In the present study, we evaluated the effects of the Limb Activation Treatment (LAT) alone and in combination with the Contralateral Arm Vibration (CAV) on left neglect (LN) rehabilitation. We conceived them as techniques that both prompt the activation of the lesioned right hemisphere because of the activation (with the LAT as an active technique) and the stimulation (with the CAV as a passive technique) of the left hemibody. To test the effect of the simultaneous use of these two techniques (i.e., LAT and CAV) on visuo-spatial aspects of LN, we described the case of a LN patient (GR), who showed high intra-individual variability (IIV) in performance. Given the high IIV of GR, we used an ABAB repeated-measures design to better define the effectiveness of the combined application of LAT and CAV, as a function of time. The results showed an improvement of GR’s performance on the Bells test following the combined application of LAT and CAV, with respect to the application of LAT alone. We did not find, however, significant effects of treatment on two other LN tests (i.e., Line bisection and Picture scanning). We propose that the combined application of LAT and CAV can be beneficial for some aspects of LN.